Optimisation of the hydrolysis of oil palm empty fruit bunch to glucose using RSM [electronic resource] - Tan, Chiew Woon, 1984- (2010)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia,2010